"But It's Not That They Don't Love Their Girls": Gender Equality, Reproductive Rights and Sex-Selective Abortion in Britain. Issue 6 (3rd October 2022) - Unnithan, Maya; Kasstan, Ben
ABSTRACT: Recent demographic analysis of sex ratios at birth in the UK has signaled the issue of "missing girls" in British Asian minority populations. This paper juxtaposes the processes of reproductive regulation set in motion by this new demographic knowledge of son preference, with lived experiences of gender equality and family-making practices. Ethnographic research conducted with British Pakistani, Indian, and Bangladeshi families reveal diverse mechanisms of family decision-making that add to and nuance the prevailing statistics. We use the lens of "gender equality" and vernacular framings of sex-selective abortion to advance conceptual understandings of son preference as increasingly disconnected from selective reproduction, at the same time as selective reproduction is connected with the governance of ethnic minority identity and reproduction.